Correlations between jets and charged particles in PbPb and pp collisions at root s(NN)=2.76 TeV - (:unkn) unknown (SPRINGER, 2016)
The quark-gluon plasma is studied via medium-induced changes to correlations between jets and charged particles in PbPb collisions compared to pp reference data. This analysis uses data sets from PbPb and pp collisions with integrated luminosities of 166 mu b(-1) and 5.3 pb(-1), respectively, collected at root s(NN) = 2.76 TeV. The angular distributions of charged particles are studied as a function of relative pseudorapidity (Delta eta) and relative azimuthal angle (Delta phi) with respect to reconstructed jet directions. Charged particles are correlated with all jets with transverse momentum (p(T)) above 120 GeV, and with the leading and subleading jets (the highest and second-highest in p(T), respectively) in a selection of back-to-back dijet events. Modifications in PbPb data relative to pp reference data are characterized as a function of PbPb collision centrality and charged particle p(T). A centrality-dependent excess of low-p(T) particles is present for all jets studied, and is most pronounced in the most central events. This excess of low-p(T) particles follows a Gaussian-like distribution around the jet axis, and extends to large relative angles of Delta eta approximate to 1 and Delta phi approximate to 1.
Keywords: Jets; Heavy-ion collision; Heavy Ion Experiments; Particle correlations and fluctuations; PLUS AU COLLISIONS; TRANSVERSE-MOMENTUM; HADRONS